2015
DOI: 10.7150/ijms.8988
|View full text |Cite
|
Sign up to set email alerts
|

High Producing Tumor Necrosis Factor Alpha Gene Alleles in Protection against Severe Manifestations of Dengue

Abstract: Dengue virus (DENV) infection usually presents with mild self-limiting dengue fever (DF). Few however, would present with the more severe form of the disease, dengue hemorrhagic fever (DHF) and dengue shock syndrome (DSS). In the present study, the association between IL-12B, IL-10 and TNF-α gene polymorphisms and dengue severity was investigated. Methods: A case-control study was performed on a total of 120 unrelated controls, 86 DF patients and 196 DHF/DSS patients. The polymorphisms in IL-12B, IL-10 and TNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 59 publications
1
14
1
Order By: Relevance
“…Other researchers have reported that cross‐reactive heterotypic antibodies from a preceding DENV infection may play important roles in development of severe dengue . This is consistent with the finding that most individuals with severe dengue have previously been exposed to dengue . In contrast, cross‐protective mAbs between two different viruses isolated from patients with dengue reportedly confer protection against Zika virus .…”
supporting
confidence: 83%
“…Other researchers have reported that cross‐reactive heterotypic antibodies from a preceding DENV infection may play important roles in development of severe dengue . This is consistent with the finding that most individuals with severe dengue have previously been exposed to dengue . In contrast, cross‐protective mAbs between two different viruses isolated from patients with dengue reportedly confer protection against Zika virus .…”
supporting
confidence: 83%
“…This would suggest that its degradation alters not only the mRNA export but also the expression of Nup98dependent genes such as CDK9, RNAPII, and HLA-DRA, which in turn regulate the expression of TNF-alpha, inducible IL-6, and IFN-gamma 62 . All these cytokines are relevant during flavivirus infection 63 and its abundance has to be evaluated after transfection with WT and mutant viral proteases.…”
Section: Discussionmentioning
confidence: 99%
“…Functional assays have shown that transient suppression of TNF-α production during the early period of ADE infection in THP-1 cells promoted the initiation of DENV replication [39]. These results were contradicted in another work, where TNF-α at high and medium concentration inhibited DENV replication in human dendritic cells, a primary DENV target cells (cited in [40]). The promoter -308A allele has been related to enhanced TNF-α gene transcriptional activity [41], and different studies have associated it with diverse dengue phenotypes or failed to do so: protective against development of DHF/DSS in Malaysia [40]; not associated in Mexico [42]; dominant model marginally protective against DF in Brazil [43]; risk factor for DHF in Venezuela [44] and Cuba [45].…”
Section: Introductionmentioning
confidence: 95%